PERENCANAAN KESEIMBANGAN LINTASAN UNTUK MENINGKATKAN EFISIENSI KERJA DENGAN MENGGUNAKAN METODE RPW - Baroto, Teguh; Maryati, Wahyu Eni (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
This rescarch aims to orange a balance production line 10 improve work efficiency to rice production output. This line balancing planning, we use Rank Position Weight ( RPW ). Using operation time data in every work station and also precedence diagram based on the shoes making process could be found elements/operation group involving a work station. With 3 cycles time such as 100,150 ang 160 seconds could be found a cycle time 150 seconds result minimum operation grouping of balance delay. From this planning could be concluded that there were 10 work stations with production output 168 part of shoes of day.